Pregunta
upstudy study bank question image url

\( \frac{x+2 y}{3}=1-\frac{x-y}{2} \) and \( \frac{x-y}{3}=-2 \)

Ask by Reyes Boone. in South Africa
Feb 25,2025

Solución de inteligencia artificial de Upstudy

Respuesta verificada por el tutor

Responder

x = 0 and y = 6

Solución

We are given the equations:   (1) (x + 2y) / 3 = 1 – (x – y) / 2   (2) (x – y) / 3 = –2 Step 1. Solve Equation (2): Multiply both sides by 3 to clear the denominator:   x – y = –6 Step 2. Substitute into Equation (1): Replace (x – y) with –6 in Equation (1):   (x + 2y) / 3 = 1 – [–6/2] Simplify the right side:   1 + 6/2 = 1 + 3 = 4 Now the equation becomes:   (x + 2y) / 3 = 4 Multiply both sides by 3:   x + 2y = 12 Step 3. Solve the system: We now have the system of equations:   a. x – y = –6   b. x + 2y = 12 Subtract equation (a) from equation (b) to eliminate x:   (x + 2y) – (x – y) = 12 – (–6)   x + 2y – x + y = 18   3y = 18 Thus, y = 6. Substitute y = 6 into equation (a):   x – 6 = –6 Add 6 to both sides:   x = 0 Solution: x = 0 and y = 6.

Respondido por UpStudy AI y revisado por un tutor profesional

error msg
Explicar
Simplifique esta solución

Bonus Knowledge

To solve the given system of equations, let's start by simplifying and rearranging the first equation: 1. From the first equation: \( \frac{x + 2y}{3} = 1 - \frac{x - y}{2} \) Multiplying the whole equation by 6 (to eliminate the denominators) gives: \( 2(x + 2y) = 6 - 3(x - y) \) Simplifying further: \( 2x + 4y = 6 - 3x + 3y \) Rearranging this becomes: \( 5x + y = 6 \). 2. The second equation is: \( \frac{x - y}{3} = -2 \) Multiplying by 3 gives: \( x - y = -6 \). Now we have a simpler system of equations: 1. \( 5x + y = 6 \) 2. \( x - y = -6 \) From the second equation, we can express \( y \) in terms of \( x \): \( y = x + 6 \). Substituting \( y \) in the first equation: \( 5x + (x + 6) = 6 \) \( 6x + 6 = 6 \) \( 6x = 0 \Rightarrow x = 0 \). Now substituting \( x = 0 \) back into \( y = x + 6 \): \( y = 0 + 6 = 6 \). Thus, the solution to the system of equations is: \( x = 0, \, y = 6 \).

¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde Hazte Premium
Estudiar puede ser una verdadera lucha
¿Por qué no estudiarlo en UpStudy?
Seleccione su plan a continuación
Prima

Puedes disfrutar

Empieza ahora
  • Explicaciones paso a paso
  • Tutores expertos en vivo 24/7
  • Número ilimitado de preguntas
  • Sin interrupciones
  • Acceso completo a Respuesta y Solución
  • Acceso completo al chat de PDF, al chat de UpStudy y al chat de navegación
Básico

Totalmente gratis pero limitado

  • Solución limitada
Bienvenido a ¡Estudia ahora!
Inicie sesión para continuar con el recorrido de Thoth AI Chat
Continuar con correo electrónico
O continuar con
Al hacer clic en "Iniciar sesión", acepta nuestros términos y condiciones. Términos de Uso & Política de privacidad